Conservation and promotion of heritage : mangrove ecology and informal on-stilt coastal water-based community of the southernmost tip of asian continent - Ahmad, Mohd. Hamdan (Fakulti Alam Bina, 2009)
TanjungPiai and Kukup are prominent mangrove retreats in the district of Pontian, Johor, Malaysia. TanjungPiai is significant place as it is the southernmost point of the Asian Continent while Kukup is unique due to its informal coastal on-stilt community settlement. TanjungPiai and Kukup are mainly for tourism and mostly guided by mangrove conservation program, thus the development is more of complimentary to the natural setting placing more emphasis towards mangrove ecology whilst blending well with the surrounding villages. Kukup on the other hand is an exciting fishing and seafood town but its accidental development is sometime seen as unruly to many visitors and government agencies. Thus, new constructive thinking must be introduced to conserve these two unique locations and at the same time redevelop TanjungPiai and Kukup Town as sustainable tourist landmarks. This paper reviews existing conformist development of both places and later discusses two different architectural thesis proposals of contemporary idea to revive and promote the two unique places. The first proposal employs sculptural architectural solution as new landmark of TanjungPiai. The defensive water edge architecture guarded the sensitive mangrove ecology by incorporating erosion control structures to improve the coastal mangrove ecology. The second proposal is in the form of interpretative heritage center for both TanjungPiai and Kukup incorporating poetic images of nature and traditional built forms into contemporary architecture expression. The paper concludes that both contemporary proposals illustrate the idea of conserving and translating the local natural and built heritages for promoting the areas as unique prime tourist locations